APLIKASI PEMBIAYAAN MUDHARABAH DAN MURABAHAH PADA BAITUL MAAL WAT TAMWIL DI KOTA TEBING TINGGI BERBASIS ANDROID - Ali Ikhwan; Aninda Muliani Harahap; Atikah Zulfi Ayuni (JISTech (Journal of Islamic Science and Technology), 2021)
Mudharabah financing is a product that is in demand by the public, especially for those who want to develop their business but do not have capital. Meanwhile, murabahah financing is a product that offers buying and selling between BMT Tebing Tinggi and members. BMT Tebing Tinggi will purchase or order goods according to the request of members, then sell them to members at the purchase price plus the agreed BMT Tebing Tinggi profit. Data processing activities on this financing product are still carried out using hand or written media, services are hampered so that members have to wait a long time. Based on this background, an Android-based mudharabah and murabahah financing application was made. In making this application, researchers used qualitative methods to analyze data using Unified Modeling Language (UML) tools. By using kodular tools, Java as the programming language and MySQL as the database. This financing application produces a system that facilitates activities that occur at BMT Tebing Tinggi such  as member registration, savings submissions, financing applications and installment payments, as well as simplifying data processing such as member data, savings, financing, and installments.